A Polyurethane/Carbon Black Composite Absorber for Low Frequency Waves - ARCA, EMİN (SPRINGER-VERLAG BERLIN, 2019)
This study proposes a Polyurethane/Carbon Black composite coating that has the ability of absorbing low frequency waves. The characteristics of coating including contact angle measurements are provided and for performance analyses, a 1 kHz amplitude-modulated signal superimposed on red and green laser beam (whose intensity is changed by square wave) sent to composite coated surface. The reflected beam from the coating was detected by BPW20RF photodetector and signal waves were measured. The results of the analyses illustrated that the composite; coating to a great extent, absorbed the waves.
Keywords: Composite coating; Absorbency; Surface energy